First‐in‐man successful use of the SPECTRUM percutaneous dual‐stage right ventricle and right atrium to pulmonary artery ventricular assist device. Issue 10 (23rd July 2022) - Usman, Asad A.; Spelde, Audrey E.; Olia, Salim E.; Cevasco, Marisa; Bermudez, Christian; Haddle, John; Ibrahim, Michael; Szeto, Wilson; Vernick, William; Gutsche, Jacob
Abstract: Background: Over the past decade, several minimally invasive mechanical support devices have been introduced into clinical practice to support the right ventricle (RV). Percutaneous cannulas are easy to insert, minimally invasive, and treat acute RV failure rapidly. In December 2021, the Food and Drug Administration approved a new 31 French dual lumen single cannula for use as a right ventricular assist device. Aims: Descirbe the use of the new dual lumen percutaneous right ventricular assist device (RVAD) cannula. Material and Methods: Deployment of the RVAD can be done surgically or percutaneously. This cannula, manufactured by Spectrum, is dual staged. It has inflow ports positioned both in the right atrium (RA) as well as the RV for maximal drainage of the right heart. The distal end of the cannula which includes the outflow port is positioned in the pulmonary artery (PA). Results: Deployment of the Spectrum RVAD can be done percutaneously with transesophageal and flouroscopy guidence. Cannulation requires requisite wire skills in order to navigate into the main pulmonary artery. Utilization of this cannula can be done in acute RV failure secondary to ischemia, post cardiotomy shock, acute respiratory failure or other causes of isolated RV failure. Discussion: The dual stage drainage design optimizes venous drainage as well as limits suck‐down events. Theoretically, direct RV decompression also decreases RV dilation and wall tension, and facilitates improved transmural pressure gradient to reduce RV strain. Conclusion: Here we describe the first‐in‐man successful use of the dual‐stage RA and RV to PA Spectrum cannula in a patient with severe COVID acute respiratory distress syndrome and acute right ventricular failure, bridged to recovery.